Ledelse af kreative kulturorganisationer: Rammebetingelser og udviklingsmuligheder for danske teaterorganisationer - Parum, Eva (Peripeti, 2009)
The paper describes and analyzes the new structures for theatre production and argues for the need of changed management principles (Culture Governance) and organizational structures for creation of future theatre production in Denmark.